The architecture of Lalbagh Fort mosque, Dhaka - Abdullah, Fadzidah; Rashid, Md. Mizanur (IIUM Press, 2011)
Heritage Studies is best learned by experiencing the architecture of the past. Thus, the instructional design of Heritage Studies course in IIUM disseminates knowledge on history of Muslim’s civilization by familiarising students on the techniques of documenting historical buildings for preservation and conservation. The architecture of Lalbagh Fort Mosque in Dhaka, Bangladesh, offers students such experience. By analysing comprehensive architectural design aspects of the Mosque, students then produce documentation of the study. This chapter specifically and briefly presents the accents of work produced on the Mosque of Lalbagh Fort. Three main aspects discussed are the space planning, structural system, and decorations of the mosques. The documentation produced by this undertaking might be used by future generation towards awareness, understanding, and appreciation of Islamic architectural heritage.